2015
DOI: 10.1007/s40279-015-0365-0
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of High-Intensity Interval Training (HIT) and Continuous Endurance Training for VO2max Improvements: A Systematic Review and Meta-Analysis of Controlled Trials

Abstract: 2 Key points When compared to no exercise, endurance training and high-intensity interval training elicit large improvements in maximal oxygen uptake. Endurance training and high-intensity interval training elicit additional benefit for individuals with lower pre-training fitness. In healthy, young to middle-aged adults, high-intensity interval training improves maximal oxygen uptake to a greater extent than traditional endurance training. 3 AbstractBackground Enhancing cardiovascular fitness can lead to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
522
14
35

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 684 publications
(610 citation statements)
references
References 60 publications
(49 reference statements)
39
522
14
35
Order By: Relevance
“…[20][21][22] It has been frequently reported in the scientific community that dynamic exercises with greater motor complexity and that resemble movements of activities of daily living are more likely to be transferred into the individuals' specific needs. 5,23 In a six-week study with application of specific exercises for activities of daily living or strength training using elastic bands, Krebs et al 7 found that although improved lower limb strength was observed in both groups, the group that performed exercises proposed in the FT presented higher gait speed, higher maximum knee torque, better dynamic balance and better coordination during the execution of tasks of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] It has been frequently reported in the scientific community that dynamic exercises with greater motor complexity and that resemble movements of activities of daily living are more likely to be transferred into the individuals' specific needs. 5,23 In a six-week study with application of specific exercises for activities of daily living or strength training using elastic bands, Krebs et al 7 found that although improved lower limb strength was observed in both groups, the group that performed exercises proposed in the FT presented higher gait speed, higher maximum knee torque, better dynamic balance and better coordination during the execution of tasks of daily living.…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49][50] In a similar comparative meta-analysis of 277 patients with CHD, Elliot and colleagues demonstrated that HIIT was associated with a significantly higher VO2, which is independently associated with reduced CVD mortality. 51 Larger national cohort studies across the globe support these findings in disease- 53,54 In case control and cohort studies of CHD patients, high intensity ET has been shown to elicit higher aerobic capacity, improved endothelial function, and enhanced HRQoL.…”
Section: Role Of Exercise Intensitymentioning
confidence: 99%
“…Continuous training (CT) is characterized by a high volume of work without any interruption, and interval training (IT) involves bursts of vigorous exercise separated by periods of rest or recovery (Bompa 2002). Most guidelines recommend the practice of CT, but recent reviews and meta-analysis suggest the superiority of IT to improve aerobic capacity, as measured in individuals by maximal oxygen consumption (Peri-Okonny et al 2015;Milanović et al 2015) and vascular function (Ramos et al 2015). Of 12 studies included in a recent review, two found no difference in BP after training, five found a greater effect from CT and five from IT, demonstrating that there is still no consensus on the best method of training to promote improvements in BP (Peri-Okonny et al 2015).…”
Section: Introductionmentioning
confidence: 99%